Digestible energy requirement for females of Rhamdia quelen on reproductive activity fed with ration based on vegetal ingredients - Bombardelli, Robie A.; Sanches, Eduardo A. [UNESP]; Tessaro, Lucelia [UNESP]; Buzzi, Alexandre H.; Martins, Cleide V. B.; Meurer, Fabio (Univ Catolica De Valparaiso, 2015)
The present experiment was carried out to evaluate the growth and reproductive parameters of Rhamdia quelen females fed with pelleted ration containing different levels of digestible energy, and to evaluate the vigor of their offspring. The breeders were placed in tanks under conditions of photoperiod and natural temperature. The fishes were fed for 255 days with isoproteic rations pelleted containing 35% of crude protein (CP) and five levels of the digestible energy (DE) (2700, 2950, 3200, 3450, 3700 kcal kg(-1)). The fishes were distributed in a randomized experimental design compounded by five treatments and three repetitions. A 16-m(2) tank containing six females and three males was considered as one experimental unit. The weight and weight gain was evaluated. During the reproductive season the females were induced to breeding by hormonal manipulation and were evaluated the percentage of spawning females, the total fecundity, relative fecundity (number of oocytes per gram of spawning females), the fertilization ratio, the time to hatching and the vigor of larvae. The growth and reproductive parameters were not influenced (P > 0.05) by the increasing levels of digestible energy of the rations. The feeding of R. quelen females in breeding fit can be carried out with 2700 kcal kg(-1) pelletized ration based on vegetal ingredients, without damage to reproductive performance.
Keywords: Rhamdia quelen; eggs; fertilization; larvae; nutrition; reproduction; aquaculture